Fabrication of Super Tough Polycarbonate/Styrene-Etylene-Butylene-Styrene Grafted Maleic Anhydride (SEBS-g-MA) Blends: Morphological, Short Term Static Mechanical and Fracture Performance Interpretation. Issue 2 (22nd January 2019) - Garhwal, Astha; Maiti, S.N.
ABSTRACT: Impact behaviours, tensile properties and fracture performance of polycarbonate (PC)/styrene ethylene-butylene-styrene-grafted-maleic anhydride (SEBS-g-MA) copolymer blends at SEBS-g-MA volume fraction Φd  = 0–0.39 are evaluated. In presence of rubber a significant augmentation in notched Izod impact strength was observed while tensile modulus and strength decreased. Morphological studies reveal good interaction between the PC and the rubber particles showing homogeneous dispersion of SEBS-g-MA in the polycarbonate matrix. Interparticle distance of the dispersed phase evaluated from the morphology studies by scanning electron microscopy (SEM) and the impact strength dependence on the concentration of the blending rubber were analysed. The essential work of fracture approach is applied to study fracture properties of the blends. With increasing SEBS-g-MA concentration nonessential or plastic work increased which explained the enhancement of impact strength of blends. GRAPHICAL ABSTRACT: